2014
DOI: 10.1111/1574-6968.12628
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic effects of hematoporphyrin monomethyl ether onStaphylococcus aureus in vitro

Abstract: This study aims to investigate the effect of hematoporphyrin monomethyl ether (HMME)-mediated sonodynamic antimicrobial chemotherapy (SACT) on Staphylococcus aureus. SACT was carried out using HMME and 1 MHz ultrasound irradiation. The bactericidal effect was evaluated by the counting colony-forming units (CFU), and important SACT parameters including ultrasound intensity and HMME concentration were determined. More than 95% of the bacteria colonies were effectively killed in the SACT group by 50 μg mL(-1) HMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…But the sensitizers have noncytotoxicity in a certain concentration range and do not damage the surrounding normal tissues [24, 25]. HMME possess a stable wavelength and a short incubation time, compared with hematoporphyrin derivative (HPD) [13]. Previous studies have indicated that the HMME concentration of 40  μ g/mL activated by laser reduced the growth of THP-1 cells [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But the sensitizers have noncytotoxicity in a certain concentration range and do not damage the surrounding normal tissues [24, 25]. HMME possess a stable wavelength and a short incubation time, compared with hematoporphyrin derivative (HPD) [13]. Previous studies have indicated that the HMME concentration of 40  μ g/mL activated by laser reduced the growth of THP-1 cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Using this technique, sonosensitizer is activated by irradiation with low-intensity ultrasound of a suitable frequency, generating reactive oxygen species (ROS), such as free radicals and singlet oxygen, to kill target cells [11]. Based on the characteristic of ultrasound, SDT has many advantages over conventional periodontal treatment, such as no drug resistance, noninvasive, easy repeatability, and strong penetrating power [13]. Recent experimental studies showed that SDT can effectively kill Staphylococcus aureus [13], methicillin-resistant Staphylococcus aureus [14], and inflammatory cells, such as U937 and THP-1 [15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou and co-workers studied the effect of hematoporphyrin monomethyl ester (HMME) in the SACT of S. aureus. 54 The authors investigated the effect of the sensitiser dose and the ultrasound dose on the cell inactivation efficacy, and they found that under the most effective SACT parameters, which involved the incubation with 50 µg/L HMME followed by US irradiation (1 MHz, 6 W/cm 2 , 30 min), the reduction in microbial load was ca. 2 log.…”
Section: Sact Mediated By Photosensitisersmentioning
confidence: 99%